An action research promoting sustainable agriculture in Barangay Loma through agricultural value chain analysis - Calanog, Michelle Jane B. (Animo Repository, 2019)
This paper discusses the promotion of sustainable agriculture in Barangay Loma through agricultural value chain analysis. Sustainable agriculture is focused on incorporation of ecologically sound, economic viability, and social equity to ensure long-term productivity of natural resources and improved livelihoods. Landowners and farmers of Barangay Loma have been experiencing decrease in agricultural return due to various factors such as low agricultural productivity and climate change. There are also limited sources of funding for capital where landowners and farmers can borrow at a low interest rate. Kotter’s theory and agricultural value chain financing framework were employed to aid the researcher in executing the project. As the project progressed, financial inclusion and the different financial products and services available to the farmers were tackled. This integrated action research project involved the creation of a strategic plan for the Barangay’s agriculture sector and a seminar for the landowners and farmers.